2020
DOI: 10.1080/14445921.2021.1943626
|View full text |Cite
|
Sign up to set email alerts
|

Different grades and different green premiums: a cross sectional analysis of a green certification scheme

Abstract: Green certification is often hailed as an effective means of resolving information asymmetry by providing prospective buyers with credible proof of a property's level of quantitative sustainability performance. These certification schemes are also considered as providing the credible identification labels needed to generate a market premium. This study analysed whether different market premiums (financial implications) exist across different ratings of the HK-BEAM certification scheme. The paper used hedonic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…There are also studies in the residential sector. Mesthrige et al [22] show the relationship between real estate price and green accreditation called BEAM-Plus in Hong Kong. The residential buildings with this rating system recorded an average increase of 6.61% in price premiums.…”
Section: Price Premiums Of Green Buildingsmentioning
confidence: 99%
“…There are also studies in the residential sector. Mesthrige et al [22] show the relationship between real estate price and green accreditation called BEAM-Plus in Hong Kong. The residential buildings with this rating system recorded an average increase of 6.61% in price premiums.…”
Section: Price Premiums Of Green Buildingsmentioning
confidence: 99%
“…Zhang et al [30], for example, found that new residential units with the Chinese Green Building Evaluation Label (GBEL) attracted a price premium of 6.9% compared with their nonlabelled counterparts. Mesthrige et al [31] found that, on average, residential units with a Hong Kong Building Environmental Assessment Method (HK-BEAM) rating attracted a 5.3% to 6.7% price premium. Further, they observed significant price premium differences across the different ratings available for HK-BEAM certified buildings.…”
Section: Sustainability Advertising In the Residential Property Sectormentioning
confidence: 99%
“…Also, the use of technologies such as solar panels reduces the energy required by the occupants of properties [13]. In recent years, researchers have shown increased interest in examining the effect of green features on the value of real estate properties [14,15]. Voicu and Been [14] evaluated the effect of communal gardens on the value of real estate properties located in New York City.…”
Section: Introductionmentioning
confidence: 99%